FRACTURE ANALYSIS OF MAIN TRANSFORMER EQUIPMENT CLAMP IN NUCLEAR POWER PLANT - ZHANG HongWu; FENG NanNan; LIU Rui; CHEN Yang (Jixie qiangdu)
Several equipment clamps of main transformer in a nuclear power company were broken. Taking samples from the broken equipment clamps and the same batch of spare equipment clamps, the fracture causes were analyzed through macroscopic inspection, penetrant testing, metallographic analysis, micro morphology testing, crimping quality testing, conductivity testing and XRD testing. The main reason for the fracture is that the equipment clamp bears all kinds of stress under the condition of insufficient strength and performance degradation, and finally cracks appear at the weakest part of the weld, forming fracture. In order to avoid the occurrence of similar accidents, it is suggested to strengthen the metal supervision and strictly control the quality of the access equipment.